Visiting Family and Friends at Desert Hot Springs - Watkins, Howard::::::::: (1978)
Albert Watkins holding Adam Watkins, Rose Watkins, Manny Krause in family 1926 Model T Ford Watkins 4-door silver Mazda RX-2 in background